Facile enantioseparation and recognition of mandelic acid and its derivatives in self‐assembly interaction with chiral ionic liquids. Issue 23 (20th October 2019) - Cai, Pengfei; Gao, Zhan; Yin, Xinchi; Luo, Yuanqing; Zhao, Xiaoyong; Pan, Yuanjiang
Abstract: Mandelic acid and its derivatives are important medical intermediates in the pharmaceutical industry. Different stereoisomers exhibited distinct biological properties to human bodies. Given that, enantioselective recognition and separation of mandelic acid are of great importance. In this study, four novel different types of chiral ionic liquids bearing designed functional groups were synthesized and successful enantioselective precipitation with mandelic acid and its derivatives. That is, (R, R)‐chiral ionic liquid 1 can coprecipitated with S‐mandelic acid and its derivatives was observed. In addition, good correlation coefficient is achieved by using electrospray mass spectrum at negative ion pattern for quick analysis of the enantioselective precipitation, which could be served as a method of enantioselective recognition. The possible intermolecular interactions are established after systematical studies by NMR spectroscopy and DFT calculations.